Pembuatan minuman teh kombucha pada siswa SMP (Universitas Pendidikan Indonesia (UPI), 2026)
This community service activity aims to improve students' knowledge and skills in understanding the concept of fermentation and practicing the making of kombucha drinks as an effort to apply a healthy lifestyle. The training was conducted using the Participatory Action Research (PAR) method, which emphasizes active involvement between students and participants in every stage of the activity. This approach was realized through interactive activities in the form of theoretical material delivery, kombucha making practice, question and answer sessions, and fermentation result evaluation. Participants gained an understanding of the fermentation process, the benefits of kombucha as a probiotic drink, and the importance of maintaining hygiene during the production process. The evaluation results showed that this activity went very well, as indicated by the high level of participant satisfaction and increased interest in making kombucha independently at home. This activity not only broadened the students' knowledge but also fostered awareness of the importance of a healthy lifestyle and scientific attitude.